BUILDING ENTREPRENEURSHIP SPIRIT THROUGH DIGITAL TECHNOLOGY BUSINESS - Diah Dinaloni; Heru Totok Tri Wahono (International Journal of Multidisciplinary Research and Literature, 2023)
Students are a very potential component of nation-building. With a young age range, strong staff, a wide enough network, and the ability to think and have high creativity, it is the foundation and basic capital for the country's progress. BPS data as of February 2020 released Indonesia's employment conditions showing the unemployment rate fell to 5.01 percent or decreased by 50 thousand people over the past year. Although the aggregate unemployment rate has decreased, judging by the level of education, more and more university graduates are unemployed. The high level of educated unemployment is because many universities graduates target that after graduation, they have to get a job armed with the knowledge they have obtained through their courses. Even though they are university graduates, it is not easy for someone to be accepted into a job, increasing the number of unemployed. By seeing these problems, it is appropriate for the government and related parties to develop a strategy to direct university graduates to become job creators, not job seekers. This underlies the importance of efforts to build an entrepreneurial spirit among students. The rise of digital technology today can be said to be a form of change management in the business world; by utilizing digital technology in the business sector, it is hoped that an entrepreneurial spirit will form among students. But unfortunately, the current conditions are where students can't take advantage of sophisticated digital technology opportunities to seize entrepreneurship opportunities and make them a livelihood. The study aimed to describe: (1) supporting and inhibiting factors in building student entrepreneurship; and (2) strategies to build student entrepreneurship through digital technology businesses. This research is a qualitative descriptive study located at STKIP PGRI Jombang. The data sources used are primary and secondary. The research subjects were entrepreneurship lecturers and students of the 2019 economic education study program who had taken theory and practice entrepreneurship courses. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use data reduction, data display, and conclusion. We are checking the research's validity using source and technique triangulation. The research results show that: (1) Supporting factors in building an entrepreneurial spirit for students of the STKIP PGRI Jombang Economic Education Study Program are (a) collaboration between universities and the business world by conducting entrepreneurial training and internships, (b) self-confidence, which is one of the capitals for opening a business, and ( c) an organization which is a forum for channeling interests and honing student skills; (2) The inhibiting factors in building the entrepreneurship spirit of students of the Economic Education Study Program STKIP PGRI Jombang are (a) the lack of a student entrepreneurship spirit which results in students choosing less to do entrepreneurship, (b) the lack of capital. In the minds of students, to start a business, they must have a large capital, and it is this thinking that must be changed by every tertiary institution, (c) the lack of entrepreneurship training in tertiary institutions; and (3) Strategies to build an entrepreneurial spirit through digital technology business for students of the Economic Education Study Program STKIP PGRI Jombang are (a) holding entrepreneurship seminars that aim to change the mindset of students, (b) holding digital technology training for students